2017
DOI: 10.15252/embj.201695776
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of formate–nitrite transporters by dielectric shift of substrate acidity

Abstract: Bacterial formate-nitrite transporters (FNTs) regulate the metabolic flow of small, weak mono-acids. Recently, the eukaryotic PfFNT was identified as the malaria parasite's lactate transporter and novel drug target. Despite crystal data, central mechanisms of FNT gating and transport remained unclear. Here, we show elucidation of the FNT transport mechanism by single-step substrate protonation involving an invariant lysine in the periplasmic vestibule. Opposing earlier gating hypotheses and electrophysiology r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(118 citation statements)
references
References 43 publications
8
109
1
Order By: Relevance
“…We found that eukaryotic PfFNT and BbFNT transport formate and acetate at the same rate, and L-lactate at about half the rate. The prokaryotic FocA equally transported formate and acetate, yet excluded L-lactate confirming earlier data [22]. NirC turned out to be selective for the smallest substrate formate, which is bioisosteric to its genuine substrate nitrite.…”
Section: Eukaryotic Fnts Conduct Larger Substrates Than Prokaryotic Fntssupporting
confidence: 85%
See 2 more Smart Citations
“…We found that eukaryotic PfFNT and BbFNT transport formate and acetate at the same rate, and L-lactate at about half the rate. The prokaryotic FocA equally transported formate and acetate, yet excluded L-lactate confirming earlier data [22]. NirC turned out to be selective for the smallest substrate formate, which is bioisosteric to its genuine substrate nitrite.…”
Section: Eukaryotic Fnts Conduct Larger Substrates Than Prokaryotic Fntssupporting
confidence: 85%
“…This is in accordance with experimental evidence from electrophysiological single channel recordings with FocA that revealed rapid opening and closing events at the millisecond scale indicating flickering side‐chain movements . As part of the transport mechanism, the flexible side chains give way to the neutral substrate species that originates from a protonation event in the vestibule . Therefore, the selective function of the lipophilic constrictions seems to reside in posing energetic barriers against the passage of charged substrates .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect not only the electrogenic anion transport of FocA and PfFNT but additionally capture the transport of the neutral acid substrate species, we used radiolabeled substrates in our assays. 3,7 Strikingly and contrary to the electrophysiology studies, we observed increasing transport rates with increasing acidity of the assay media. Apparently, neither FocA nor PfFNT exhibited closure or gating.…”
contrasting
confidence: 99%
“…Further, the alkalization of the media during transport indicated that protons are co-transported with the substrate and disruption of the transmembrane proton gradient revealed that transport is driven by a proton-motive force. 7 Together, our data show that FNTs act as non-gated anion/proton co-transporters and the major portion of the substrate is transported as the protonated, neutral monoacid.…”
mentioning
confidence: 59%